Mechanical performance research of friction stir welding robot for aerospace applications. (28th February 2021) - Luo, Haitao; Zhao, Fengqun; Guo, Siwei; Yu, Changshuai; Liu, Guangming; Wu, Tingke
The friction stir welding robot for aerospace applications developed by the research group is subject to the effects of size, working conditions, and other conditions during the operation. The load conditions of the friction stir welding robot are harsh, and the strength and stiffness tests of the whole machine need to be carried out. Five typical working conditions of the friction stir welding robot are analyzed. By analyzing the system composition and configuration of the robot, the loading conditions of the robot stirring head during the welding process are accurately simulated, and this is used as the stiffness and strength check. The boundary conditions of the robot are simulated and analyzed under typical working conditions. The results show that the data of each part of the robot under load are obtained for a given size of the rocket cap welding. After analysis, the maximum normal displacement of the friction stir welding robot reached 0.6424 mm and the maximum stress was 79.21 MPa under the condition of melon flap welding.